PENGARUH KETERIKATAN ORGANISASI TERHADAP KEPUASAN KERJA DAN PENGARUHNYA TERHADAP KOMITMEN AFEKTIF. (SURVEY PADA KARYAWAN PT. CAHAYA SURYA SENTOSA AREA MADURA) - Alfi Hasaniyah; Citra Larashati Surya; Ummi Wahyuni (Institut Dirosat Islamiyah Al-Amien Prenduan Sumenep, 2022)
The purpose of this study was to determine the effect of organizational engagement on job satisfaction and its effect on affective commitment. This research is classified as Explanatory Research with a quantitative approach. The sample used is 98 employees of PT. Cahaya Surya Sentosa Area Madura with Purposive Sampling technique. The type of data used is primary data, namely data collection using a questionnaire. Analysis of the data used is Multiple Linear Regression with SPSS. The results of this study indicate that organizational engagement has a positive and significant effect on job satisfaction, job satisfaction has a positive and significant effect on affective commitment, and organizational engagement has a positive and significant effect on affective commitment through job satisfaction.